Nitrate in groundwater and integration of nitrogen-catch crop in rice-sweet pepper cropping system - Shrestha, R.K.; Ladha, J.K. (Wiley, 1998)
In the intensive rice (Oryza sativa L.)‐based cropping systems of the tropics, dry season (DS) nonrice crop‐fallow (dry‐to‐wet [DTW] transition)‐wet season (WS) rice is a common practice. Excessive use of N fertilizer in high‐value crops like vegetables grown in DS is economically motivated. The risk of NO3 leaching into groundwater during DTW transition is an environmental concern. Experiments were conducted in seven rice‐sweet pepper (Capsicum annuum L. var. annuum) farmers' fields to determine (i) the extent of NO3‐N contamination in groundwater, and (ii) the effectiveness of a N‐catch crop to decrease NO3 leaching. Twelve of twenty water sources had near or above World Health Organization's (WHO) NO3‐N limit for drinking water. Soil mineral N (upper 100 cm) ranged from 111 to 694 kg ha‐1 was decreased by 10 to 68% in plots with DTW crop. In fallow plots where mineral N was either maintained or increased, there was movement to lower soil profile demonstrating NO3 leaching without a crop. On average, maize (Zea mays L.) captured 176 kg N ha‐1 and indigo (Indigofera tinctoria L.) 194 kg N ha‐1. Indigo acquired <20% N from biological N fixation (BNF); this low contribution was due to inhibition by high soil mineral N. In both fallow and planted plots, mineral N declined to low levels at 100% water‐filled pore spaces (WFPS) before rice transplanting. A suggestion for developing indigo plus maize N‐catch crop rotations is made to decrease NO3 leaching and maximize N use efficiency in rice‐sweet pepper cropping system.